Target expression, generation, preclinical activity, and pharmacokinetics of the BCMA-T cell bispecific antibody EM801 for multiple myeloma treatment - Seckinger, Anja; Delgado, Jose Antonio; Moser, Samuel; Moreno, Laura; Neuber, Brigitte; Grab, Anna Luise; Lipp, Susanne; Merino, Juana; Prosper, Felipe; Emde-Rajaratnam, Martina; Delon, Camille; Latzko, Melanie; et al. (Cancer cell, 2017)
Summary: We identified B cell maturation antigen (BCMA) as a potential therapeutic target in 778 newly diagnosed and relapsed myeloma patients. We constructed an IgG-based BCMA-T cell bispecific antibody (EM801) and showed that it increased CD3+ T cell/myeloma cell crosslinking, followed by CD4+/CD8+ T cell activation, and secretion of interferon-γ, granzyme B, and perforin. This effect is CD4 and CD8 T cell mediated. EM801 induced, at nanomolar concentrations, myeloma cell death by autologous T cells in 34 of 43 bone marrow aspirates, including those from high-risk patients and patients after multiple lines of treatment, tumor regression in six of nine mice in a myeloma xenograft model, and depletion of BCMA+ cells in cynomolgus monkeys. Pharmacokinetics and pharmacodynamics indicate weekly intravenous/subcutaneous administration.